The Age Limit for Familial Prostate Cancer Screening - Fatemeh Khatami; Rouhollah Afsari; Alireza Khajavi; Seyed Mohammad Kazem Aghamir (Babol University of Medical Sciences, 2025)
prostate cancer screening should start five years before the incidence age of prostate cancer in his brothers.  The age and Gleason score of onsets in familial prostate cancer can provide critical background data for the exact age of screening and diagnostic stages.